Systematic Analysis Of Cost Effectiveness Analysis (Cea) In Health Services: A Review Of National And International Literature - Azzah Alimatusholehah (International Journal of Health Engineering and Technology, 2026)
Limited resources and the high burden of disease in Indonesia have prompted the need for economic evaluation in healthcare services. Cost-effectiveness analysis (CEA) is an important approach to assess health interventions in terms of efficiency and impact on clinical outcomes. This study aims to identify and synthesize findings from various studies related to CEA in healthcare interventions in Indonesia. This study used a systematic review method by searching literature from Google Scholar, PubMed, and Science Direct databases. Selection was carried out through the PRISMA stages starting from identification, screening titles and abstracts, to full-text selection, resulting in 9 articles that met the inclusion criteria. Most studies showed that health interventions such as immunization, tuberculosis treatment, diabetes screening, hypertension treatment, and HIV/AIDS services have high cost-effectiveness. Combination therapies or technology-based approaches such as telemedicine have also proven efficient in managing chronic diseases. The evaluation results using ICER and ACER indicators showed that most interventions were cost-effective compared to standard approaches or no intervention at all. CEA is an important tool in supporting evidence-based decision-making in the healthcare sector. Implementing CEA results can help governments and policymakers determine priority interventions that have a significant impact on service quality and budget efficiency.